Land fragmentation of agricultural enterprises in the context of administration of land - Popov, Andriy; Koshkalda, Iryna; Kniaz, Oleksandr; Trehub, Olena; Попов, Андрій Сергійович; Кошкалда, І. В.; Князь, О. В.; Трегуб, О. М. (Kyiv, Ukraine & Rzeszow, Poland : Institute of Society Transformation, 2019)
UA: В умовах суцільної оренди сільськогосподарських земель в Україні, оренду розглядають як інструмент об’єднання земельних ділянок у цілісні поля. Однак наслідки суцільної оренди земельних ділянок сільськогосподарськими підприємствами мають як позитивні, так і негативні наслідки. Дане дослідження вивчає, як сучасна система адміністрування земельними ресурсами відповідає запитам фрагментації земель та з якими проблемами стикаються сільськогосподарські підприємства при укладанні договорів оренди в умовах фрагментації земель в Україні. Отримані дані свідчать про те, що сучасна система адміністрування земельних ресурсів в Україні має ознаки прозорості та ефективності, проте не відповідає запитам фрагментації власності у землекористуванні сільськогосподарських підприємств (запропонованому новому типу фрагментації). Дослідження показали, що витрати на реєстрацію права оренди земельної ділянки державної форми власності, порівнюючи з приватними ділянками, є значно меншими у розрахунку на одиницю площі. Пропонується запровадити для сільськогосподарських підприємств окрему адміністративну послугу з реєстрації прав оренди, яка б забезпечила одночасне проходження процедури реєстрації усіх земельних ділянок у встановлений законодавством термін. EN: Introduction. Under the conditions of the excessive lease of the agricultural land in Ukraine, leasing is identified as a tool for amalgamation of land parcels into one field. However, the consequences of excessive land lease by the agricultural enterprises are both positive and negative. Often the negative consequences of such leasing lack attention from the part of policy makers and scientists. The purpose of this study is to examine how the land administration system matches the land fragmentation and what problems are faced by agricultural enterprises when concluding lease contracts under the conditions of land fragmentation in Ukraine. Results. The obtained data testify that the land administration system in Ukraine has signs of transparency and efficiency. However, the system of land administration does not meet the requirements of the ownership fragmentation in land use of agricultural enterprises. Thus, the registration of lease rights to hundreds of the land parcels requires considerable costs and time. The long-lasting registration of the lease rights to the land parcels forces the lessees to use them illegally during the registration procedure. It has been determined that the expenditures on the registration of the lease right to the state-owned land parcel are much lower in comparison with the registration of private parcels. Conclusions. One of the ways to reduce the time and cost of the registration of land parcels and rights to them is to increase the size of the land parcel per one landowner, thus reducing the number of the leased parcels in the structure of the agricultural enterprise. It is convenient to introduce a special administrative service aimed at registering lease rights of agricultural enterprises.
Фрагментація земель сільськогосподарських підприємств у контексті адміністрування земельних ресурсів
Keywords: фрагментація земель; адміністрування земельних ресурсів; реєстрація; право оренди; земельна ділянка; витрати; Land Fragmentation; Land Administration; Registration; Lease Right; Land Parcel; Costs